Analyzing the fractional order T. Regge problem using the Laplace transformation method - Hilmi, Hozan; Jwamer , Karwan H. F.; Faraj, Bawar Mohammed (Journal of Innovative Applied Mathematics and Computational Sciences, 2024)
This study uses the Laplace transformation method to solve the fractional-order T. Regge problem. In this paper, we develop formulations for the fractional Laplace transform applied to fractional integrals and derivatives, and we use this method to solve the T. Regge problem. Moreover, several examples are presented to demonstrate the method's value and effectiveness. Examples prove that the Laplace transformation method significantly advances the fractional computation field and can potentially solve fractional differential equations (FDEs). On the other hand, the advantages and disadvantages of the method are provided.